Menggagas Bentuk Ruang Kota Alternatif: Upaya Mereduksi Intensitas Pegerakan Lalu Lintas Kota - Iwan P. Kusumantoro (Journal of Regional and City Planning, 2007)
This paper aims to provide answerto the classical questions of the impact  of    spatial  design  or  urban  form  to   induce  trip  pattern. How  policy  makers  should  be advised  with  regard  to  the  use  of urban spatial structure design and land use tools to reduce traffic in urban area? Although some relationships between land use and travel  appear  straight  forward,  such  as  density  and  trip  lenght these  simple  observed  correlations  are not  so  simple  upon closer examination.  Land  use  and  travel  linkages  are  both multidimensional  and  difficult  to  deconstruct.  Rather,  they represent  complex  interactions  of  many  factors.  How  should researchers  proceed?  Any  empirical  work  of  this  nature  is problematic  given the  enormous  complexity of  the activities to be explained  and  difficulties  in conceptualizing  the  interaction between  travel  and  spatial  structure.  The  usefulness  of  land  use and  transportation  approaches,  including  alternatives  approach such  as  new  urbanism  and  smart  growth,  is  frequently  assessed based  on  the  capacity  of  these  innovations  to  reduce  auto  use. Compaction  is  a  typical  structure  of  an  alternatives  approach of urban  form.  The  preliminary   finding  of  the  research  in  the surrounding  areas  of  Bandung,  Semarang,  and  Cilegon,  shows  a different  conclusion  with  the  theoritical  description  of "compaction".  The  research  shows  that  several  local characteristics, such as threshold area, residential characteristics, facility sufficiency, and degree of area dependency have significant influences  on  travel  pattern.  This knowledge  is  needed to  explain how  travel behavior  modification  can  be  conducted  through physical design approach.